Electrostatic precipitation (ESP) index driven bio-aerosol collection for a high biological viability sampling - Zhang, Shuo; Li, Shuran; Xu, Yuzhen; Du, Yanyan; Wang, Anyu; Liu, Zhen; Yan, Keping (Journal of cleaner production, 2023)
In this work, a two-stage electrostatic precipitator as the integration of a pre-charger and an electrostatic collector is proposed for airborne bio-aerosol sampling, where a pre-charger was applied for collection efficiencies enhancement and the following parallel-plate collector captured bio-aerosols with high biological viabilities. And the effects of operation parameters, including applied voltages, flow rates and collection area, on both the physical collection efficiency and biological viability are investigated. Specifically, the electric field strength of 4.3 kV/cm keeps the best balance between sampling efficiency and microorganism survival. For general designs and applications of present two-stage sampler, the modified ESP index and Pre-charger index are defined based on the charging characteristics of two typical bio-aerosols as Escherichia Coli and Candida albicans for predicting physical collection efficiency, biological viability and their ratio. A porotype with 2 × 1012 s V2 m−3 and 1.5 × 1014 s V2 m−5 for ESP and Pre-charging Index, respectively, obtains collection performance 3–5 times higher than conventional AGI-30 sampler during an on-site sampling, proving its feasibility for bio-aerosol collection. [Display omitted] •An electrostatic method for E.Coli and C.albicans collection with both high efficiency and biological viabilities.•The precharger was introduced upstream collector to promote collection efficiency by the enhancement of charge carried.•The ESP index and Pre-charger index were modified concerning both bacterium survival and physical collection efficiency.•Studied system presents excellent collection behavior of microorganisms from different places inside.